2019
DOI: 10.1186/s13063-019-3745-1
|View full text |Cite
|
Sign up to set email alerts
|

Functional electrical stimulation-assisted cycle ergometry in the critically ill: protocol for a randomized controlled trial

Abstract: BackgroundIntensive care unit (ICU)-acquired weakness is the most important cause of failed functional outcome in survivors of critical care. Most damage occurs during the first week when patients are not cooperative enough with conventional rehabilitation. Functional electrical stimulation-assisted cycle ergometry (FES-CE) applied within 48 h of ICU admission may improve muscle function and long-term outcome.MethodsAn assessor-blinded, pragmatic, single-centre randomized controlled trial will be performed. Ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…gov and the full protocol has been published. 32 We used a deferred consent procedure, where patients without capacity were enrolled based on assent gained from legal representatives and asked to provide consent as soon as they regained capacity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…gov and the full protocol has been published. 32 We used a deferred consent procedure, where patients without capacity were enrolled based on assent gained from legal representatives and asked to provide consent as soon as they regained capacity.…”
Section: Methodsmentioning
confidence: 99%
“…Study subject characteristics IAPA ranges 0-8 with higher number meaning higher functional independence32 ; RAPA score ranges from 1 'I almost never do any physical activities' to 5 'I do 30 min or more per day of moderate physical activity 5 or more days per week'33 .…”
mentioning
confidence: 99%
“…FES cycling was performed 90min/day for 7 days/week. Full details including ethical approval are available in the study protocol and the original publication [ 26 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…We performed an a priori planned secondary analysis of an outcome‐based, prospective, randomized controlled trial, Electric Mobility and Insulin Resistance (EMIR; ClinicalTrials.gov, NCT02864745), performed in the ICU of FNKV University Hospital in Prague, Czech Republic. Clinical outcomes are reported elsewhere [Waldauf, Thorax 2021], the full protocol of the study has been published, 7 and details can also be found in the supplementary materials.…”
Section: Methodsmentioning
confidence: 99%
“…Animal studies suggest that mechano‐signaling pathways exist in skeletal muscle and can circumvent molecular pathways affected by insulin resistance 6 . Technology advances, such as functional electrical stimulation–assisted cycle ergometry (FESCE), allow the delivery of active exercise even before the patient regains consciousness, 7,8 and it is tempting to hypothesize that compared with standard of care, an FESCE‐based early‐mobility program delivered to mechanically ventilated patients would reduce intravenous insulin requirements and increase insulin‐mediated glucose disposal during hyperinsulinemic clamp. In this study, we also aimed to investigate the dynamics of insulin sensitivity during and 6 months after critical illness.…”
Section: Introductionmentioning
confidence: 99%